11 - Creativity Within Limits: Does the South African PhD Facilitate Creativity in Research? - Judy Backhouse, (Journal of Higher Education in Africa, 2009)
One view of the PhD student is that of the independent scholar, with the thesis being an original work that contributes to the body of knowledge. National plans make much of the notion that graduating doctoral students will increase the degree of innovation in the country and make new ideas available for economic benefit. At the same time, the process of completing a PhD takes place within frameworks of institutional and disciplinary tradition; student and supervisor expectations, practi- cal resource limitations and, increasingly, national and international quality stan- dards – all of which place boundaries on what can be studied and how it can be studied. Based on interviews with doctoral students at South African universities, this paper explores the extent to which they experience themselves as independent scholars and the role of creativity in their PhD studies. It explores the boundaries that limit creativity in doctoral programmes and whether PhD candidates experience these boundaries as restrictive or not. It asks whether innovation can realistically be expected to result from doctoral programmes.